PENGARUH JENIS WELDING GROOVE TERHADAP KEKUATAN IMPACT PLAT BAJA ASTM A36 MENGGUNAKAN MESIN LAS SMAW - Ariyanto Ariyanto; Tati Noviati (Asosiasi Dosen Muda Indonesia, 2025)
Currently, metal joining with welding process is increasingly used, both in building construction, piping, and machine construction. This is due to the many advantages obtained from joining by welding. The use of the right welding groove will also affect the welding results. The purpose of using welding groove is for the place to fill the welding material and can also strengthen the design of the metal joint. Welding groove plays an important role in improving the design and properties of the joint in the welding process. ASTM A36 welding using SMAW welding current 110 A is carried out with Groove variations, namely VGroove, Square Groove, and Bevel Groove and using E6013 electrodes with a diameter of 2.6 mm. The purpose of this study was to determine the strength of SMAW welding joints on ASTM A36 against the Charphy impact test. the required impact charphy effort results (W) are on V Groove of 73.519 J, Square Groove of 67.43 J, and Bevel Groove of 70.485 J. And produces an impact charphy value (K) on V Groove of 0.918 J / ????????2, on Square Groove of 0.842 J / ????????2 and on Bevel Groove of 0.881 J / ????????2. The impact charphy value on V Groove with SMAW welding current of 110 A on ASTM A36 carbon steel is the best with the required impact charphy results (W) namely on V Groove of 73.519 J and the impact charphy value (K) on V Groove of 0.918 J / ????????2.